Kedudukan Hukum Pemegang Polis Pada Perusahaan Asuransi yang Dinyatakan Pailit - Ni Kadek Vikka Ayu Swandewi; Ni Luh Made Mahendrawati; I Putu Gede Seputra (Jurnal Konstruksi Hukum, 2021)
In this era of globalization, insurance has been considered as a basic need which is a human need for security. Insurance is a form of risk management that is formed with the aim of avoiding the possibility of an uncertain risk of loss. This study aims to examine the legal position of policyholders as creditors in insurance companies and to reveal the legal protection of policyholders in insurance companies that are declared bankrupt. This study uses a normative research method because there is still a conflict of norms, with the approach to legislation. The data is sourced from the opinions of legal scholars and data law. The data sources are primary and secondary data obtained through recording and documentation, then the data is processed using interpretation and descriptive. Based on the Bankruptcy Law and PKPU Article 1 number 2, creditors are parties who have receivables due to agreements or laws that can be collected in advance of services. In the context of the legal protection of the policyholder, the Insurance Act has regulated the existence of a policy guarantor institution in which the purpose of the establishment of a policy guarantee program is to guarantee the return of part or all of the rights of the policyholder. In the bankruptcy and liquidation of an Insurance Company, it is expected that the curator will pay attention to the right of the Policy Holder to obtain compensation from the bankruptcy assets of the Insurance Company.